Secondary metabolite profiling of four host plants leaves of wild silk moth Attacus atlas L. - Lisna Hidayati; Tri Rini Nuringtyas (Universitas Gadjah Mada, 2016)
Secondary metabolites may affect insect herbivores’ host plant preferences. Attacus atlas L. larvae are known have a wider variety of host plants compared with other members of the Attacus genus. This research compared the metabolic profiles of four A. atlas host plants: keben (Barringtonia asiatica (L.) Kurz), dadap (Erythrina lithosperma Miq.), gempol (Nauclea orientalis L.), and soursop (Annona muricata L.). Leaves were collected from Sawit Sari Research Station, Yogyakarta. Terpenoid was extracted by macerating the leaves in ethyl acetate and subjecting them to GC-MS analysis, while alkaloid, tannin, and flavonoid were extracted through percolation. Total alkaloids, tannins, and flavonoids were measured using spectrophotometric analysis. Multivariate data analysis using PAST ver. 3.0 was performed on the GC-MS data. Based on the PCA scatter plot of the GC-MS data, keben leaves were clustered separately from the other three leaves by PC1. Dadap and gempol leaves were clustered together due to the phytol content while caryophyllene was detected only in soursop leaves. Neophytadiene was detected in all of the leaves, suggesting that this terpenoid may serve as a signal to locate the host plants. Keben leaves contained the lowest alkaloids and highest tannins and flavonoids compared with the other leaves. These secondary metabolites may determine the host plant suitability for culturing the A. atlas.